Future directions in Antarctic psychology research - Kimberley Norris; Douglas Paton; Ayton, J (2010)
Although existing research regarding the experience of Antarctic employment has primarily focused on the absence period (i.e. the period of time in which the expeditioner physically works in Antarctica), it has been repeatedly demonstrated that the majority of expeditioners experience positive outcomes associated with their time on the ice despite transient (and frequently subclinical) physical, psychological, and social difficulties. Research strategies directed towards the individual experience of the expeditioner have not been able to fully account for the processes underpinning the adjustment processes that have facilitated seemingly resilient and growth outcomes. Similarly, insufficient research attention has been given to the separate phases of Antarctic employment, nor the potential interdependence between them, which may also provide further insight into these processes. To address these issues it has been argued that an approach incorporating individual, interpersonal, and organizational factors throughout the Antarctic employment experience, from pre-departure through absence, reunion, and reintegration, be adopted. Â© 2010 Antarctic Science Ltd.